Innovative Strategies of Sign Language Interpretation Services to Optimize Learning for Deaf Students in Inclusive Classrooms: An In-Depth Study in Inclusive Schools - Charles, Jane; Bali, Theodora; Sungwa, Reuben (Universitas Nurul Jadid, 2024)
This study focuses on exploring the effectiveness of sign language interpretation services in supporting the learning involvement of deaf students in inclusive classrooms. In the context of the limited number of professionals who are proficient in sign language, this study examines the role of peers, the use of local signs, and guest speakers as alternative interpretations applied in inclusive schools. This research uses a qualitative method with a phenomenological approach, which allows for deepening the experiences and perceptions of various related parties, including deaf students, teachers, and school principals. Data were collected through in-depth interviews and direct observation in two inclusive schools in a specific region, involving 32 participants consisting of principals, sign language teachers, non-professional teachers, and deaf students. The data analysis technique used is the thematic analysis of Miles and Huberman, which includes the stages of data reduction, data presentation, and conclusion drawing and verification. The results showed that although peers and local signs helped with minimal involvement of deaf students, the presence of professional sign language teachers was more effective in ensuring a deep understanding of the subject matter. In addition, guest speakers from local education offices contribute positively to learning, despite limited availability and lack of sustainability. These findings underscore the importance of developing comprehensive and professional interpretation services in creating an inclusive educational environment. The implications of this study are the need for long-term strategies involving peer training and recruitment of professional sign language teachers to support the learning engagement of deaf students, as well as the provision of policies that are responsive to the communication needs of students with special needs in inclusive schools.